Extracellular Cues Influencing Oligodendrocyte Differentiation and (Re)myelination - Wheeler, Natalie A. (Exp Neurol, 2016)
There is an increasing number of neurologic disorders found to be associated with loss and/or dysfunction of the CNS myelin sheath, ranging from the classic demyelinating disease, Multiple Sclerosis, through CNS injury, to neuropsychiatric diseases. The disabling burden of these diseases has sparked a growing interest in gaining a better understanding of the molecular mechanisms regulating the differentiation of the myelinating cells of the CNS, oligodendrocytes (OLGs), and the process of (re)myelination. In this context, the importance of the extracellular milieu is becoming increasingly recognized. Under pathological conditions, changes in inhibitory as well as permissive/promotional cues are thought to lead to an overall extracellular environment that is obstructive for the regeneration of the myelin sheath. Given the general view that remyelination is, even though limited in human, a natural response to demyelination, targeting pathologically ‘dysregulated’ extracellular cues and their downstream pathways is regarded as a promising approach toward the enhancement of remyelination by endogenous (or if necessary transplanted) OLG progenitor cells. In this review, we will introduce the extracellular cues that have been implicated in the modulation of (re)myelination. These cues can be soluble, part of the extracellular matrix (ECM) or mediators of cell-cell interactions. Their inhibitory and permissive/promotional roles with regard to remyelination as well as their potential for therapeutic intervention will be discussed.